Fields of Educational Interest and an Islamist Orientation in Australia - Satterley, Shane (Terrorism and political violence, 2023)
This article contributes to our understanding of Islamist extremism by examining the relationship between early educational interests and ideas associated with Islamist-jihadist ideology. The article uses data collected through the Islam in Australia survey and specifically compares STEM (science, technology, engineering and mathematics) with HSS (humanities and social science) fields of educational interest in relation to respondents’ identification with political Islamist and militant typologies, identification with Islam as a political system, understandings of jihad and views on the caliphate as an Islamic religious obligation. The article found Muslim Australians who expressed an interest in STEM fields at high school were more likely than those interested in HSS to: (1) identify with the political Islamist and militant typology; (2) believe Islam advocates a political system; (3) believe establishing a caliphate is a religious obligation; and (4) define jihad as defensive and offensive rather than as defensive only. As discussed in the article, these findings support those of other research), which have identified an overrepresentation of STEM and an underrepresentation of HSS among Islamist-jihadists. This article adds weight to the assertion that the mindset of Islamist-jihadists, may be present prior to undertaking tertiary education and may predispose some to support extremist ideologies. This paper finds that an Islamist-jihadist ideological orientation has a relationship with the STEM fields broadly and Islamic studies specifically during adolescence.